1996
DOI: 10.1007/bf01981811
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of Ni(II) and Fe(III) acetates and their mixture

Abstract: The thermal decomposition of the ferric and nickel acetate salts has been followed. It was found that the heating rate affects the decomposition steps. For a heating rate of 1 K min -I the product is either Fe203 or NiO. For a higher heating rate the suboxides are obtained and reoxidized again on further heating. The decomposition of the mixed salt is an overlap of the DTA for the separate salts but the decomposition reactions are shifted to lower temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 4 publications
(1 reference statement)
1
17
2
Order By: Relevance
“…In studies on the physical and chemical properties and the structures of solid complexes of transition metal ions with organic ligands, it is customary to investigate the thermal decomposition of these complexes so as to obtain useful data on the metal-ligand bonds [2][3][4] and stability trends. The thermal investigations on some derivatives of amines [5], sulfonamides [6], substituted thiourea salts [7], and complexes of bidentate ligands and others [8][9][10][11][12][13], have already been published.…”
Section: Introductionmentioning
confidence: 99%
“…In studies on the physical and chemical properties and the structures of solid complexes of transition metal ions with organic ligands, it is customary to investigate the thermal decomposition of these complexes so as to obtain useful data on the metal-ligand bonds [2][3][4] and stability trends. The thermal investigations on some derivatives of amines [5], sulfonamides [6], substituted thiourea salts [7], and complexes of bidentate ligands and others [8][9][10][11][12][13], have already been published.…”
Section: Introductionmentioning
confidence: 99%
“…After saturation, disk pallets were dried in 240°C and calcinated at 800°C in 10%H 2 /90%Ar mixture. The drying temperature was determined from TG/DTA curves of decomposition nickel nitrate in air atmosphere presented by Elmasary et al [19]. According to Elmasary, 240°C is a sufficient temperature for complete decomposition of nickel , platinum crucibles nitrate.…”
Section: Methods II (M Ii)mentioning
confidence: 99%
“…Oxalate salts are often used to obtain oxides [14][15][16][17][18]. Nickel oxalate, in contrast to the most d-electron metal salts, decomposes to metallic nickel instead of nickel oxide in inert atmosphere [19]. The results of measurements concerning the structure, microstructure, thermal, and electrical properties of the Ni/YSZ anode material testify to the usefulness of the oxalate and impregnation method.…”
Section: Introductionmentioning
confidence: 99%
“…To produce nanosized ferrite particles, some techniques such as chemical coprecipitation [3][4][5], hydrothermal synthesis [6], sol-gel [7,8] and freeze-drying of metal carboxylate solution [9] methods have been developed. Starting from metal carboxylate precursors, the authors commonly found that the composition of the oxide products depends considerably on the reaction conditions in the synthesis [10][11][12]. For instance, Elmasry and coworkers [10] found that the high rate of heating (above 10K/min) causes the increase of the decomposition temperature and the metal ions in the products are partially reduced.…”
Section: Introductionmentioning
confidence: 98%
“…Starting from metal carboxylate precursors, the authors commonly found that the composition of the oxide products depends considerably on the reaction conditions in the synthesis [10][11][12]. For instance, Elmasry and coworkers [10] found that the high rate of heating (above 10K/min) causes the increase of the decomposition temperature and the metal ions in the products are partially reduced. In such cases it has generally been proven that the reoxidation of the product takes place during further heating and enables the segregation of α-Fe 2 O 3 [13,14].…”
Section: Introductionmentioning
confidence: 98%